2003
DOI: 10.6009/jjrt.kj00003174160
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Imaging Posture Using Modified Oblique View of the Axilla (MOVA) for Sentinel Lymph Node Scintigraphy in Patients with Breast Cancer

Abstract: Identification of the sentinel lymph nodes in patients with breast cancer is often hampered by high radioactivity from the injection site, since the distance between the injection site and regional lymph nodes is quite short in these patients. We investigated the usefulness of the modified oblique view of the axilla (MOVA) method introduced by Haigh et al., aiming at better discrimination of the target and higher resolution. Compared with the standard anterior view (SAV) of the supine position and conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Consequently, identification of axillary SLNs was equivalent with MOVA and anterior view in 18 (24%) of 75 patients, was better with MOVA in 20 (26%) patients, and was achieved only with MOVA in 38 (50%) patients. Ichihara et al 13 confirmed the usefulness of MOVA, and proposed the combined application of MOVA and anterior view because SLN detection with γ-probe during surgery is performed in a supine position.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Consequently, identification of axillary SLNs was equivalent with MOVA and anterior view in 18 (24%) of 75 patients, was better with MOVA in 20 (26%) patients, and was achieved only with MOVA in 38 (50%) patients. Ichihara et al 13 confirmed the usefulness of MOVA, and proposed the combined application of MOVA and anterior view because SLN detection with γ-probe during surgery is performed in a supine position.…”
Section: Discussionmentioning
confidence: 91%
“…Some authors reported that addition of oblique view imaging to anterior view imaging in the conventional supine position improves the diagnostic accuracy. [11][12][13] On imaging, a lead shield is used to cover the injection site with a high level of radioactivity. However, use of a lead shield has a disadvantage in that it may cover lymph nodes on images.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several papers [8][9][10][11][12] reported that modifying the imaging position improved the accuracy of SLN detection. As these methods increased the distance between the C region and axilla by modifying the imaging position, scattering from the injection site could be avoided.…”
Section: Figurementioning
confidence: 99%
“…To address this disadvantage, multiple methods [7][8][9][10][11][12][13][14][15][16][17][18] have been developed to minimize the effects of scattering and to improve SLN visibility during lymphoscintigraphy imaging. However, the use of these methods requires a new imaging in addition to as the usual imaging.…”
Section: Introductionmentioning
confidence: 99%